Traditional Games and the Formation of National Sports in Kyrgyz Culture - Arstanbek Kasenovich Ilebayev (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
The article explores national sports as an integral component of cultural heritage and the historical development of physical culture in Kyrgyz society. Particular attention is paid to the transformation of traditional Kyrgyz games and household entertainments into organized national sports. The study examines the origins of sport as a regulated form of competition, tracing its evolution from ancient ritualized and everyday practices to modern institutionalized disciplines. Using historical descriptions, ethnographic evidence, and oral testimonies, the article analyzes strength-based traditional games connected with pulling objects and everyday tools, including sticks, whips, and animal hides. Special focus is given to traditional practices that later formed the foundation of the national sport known as tayak tartysh (stick pulling). The article demonstrates that the institutionalization of national sports contributes to preserving intangible cultural heritage, strengthening national identity, and promoting physical development in contemporary society. At the same time, the transition from informal entertainment to standardized sport reshapes the original cultural functions of the games and introduces new requirements related to rules, safety, and competition formats.